University Governance Reforms in Kazakhstan - Bilyalov, Darkhan (International Higher Education, 2016)
This article depicts the country’s efforts to loose centralized state control and grant more autonomy to higher education institutions. It explains the rationale for these reforms and how the traditional structure and individual actors in university governance have shaped the context and culture of the educational landscape. The author discusses evolution of corporate governance implementation and provides analysis of both the challenges of the process and positive developments resulting from it. He argues that lessons learned from Kazakhstan’s reform might be instrumental for other countries sharing the legacy of the soviet governance system.